ارتباط اللغة العربية الكلاسيكية واللغة العربية الفصحى المعاصرة وتعليمها - rizqi, muhammad rizal (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
The Arabic language is growing and spreading widely in the world, as it is the first official language in 22 sovereign Arab countries. It is spoken by more than 470 million people. In addition, the Arabic language, specifically Classical Arabic, is the language of the religion of Islam, which is embraced by about one and a half billion Muslims, and in which they perform their religious worship. On the other hand, the United Nations considers the Arabic language to be a gateway to the rich and diverse Arab cultural heritage, and through it the bonds of cooperation between peoples are achieved and peace and peace are established. Therefore, the organization decided that the Arabic language would become one of its official languages ​​approved in 1973. There is no doubt, then, that the Arabic language has global and local importance, as departments have been allocated to teach it in American, European, Chinese, and Russian universities, to name a few. Although the Arabic language has three basic forms: the classical classical language, the modern classical language, and the colloquial languages, the modern standard language is the language spoken at the official level and in teaching and learning platforms. With the development of technical tools and artistic methods, learning classical Arabic and even its various colloquial dialects has become popular in the digital world. It is possible to learn the Arabic language electronically and attend Arabic language lessons online. Today's digital development makes it easy to communicate with professors interact with them. With the use of smart and cheerful methods, learning the Arabic language has become easier and more enjoyable than ever before.